2008
DOI: 10.1016/j.fertnstert.2007.04.060
|View full text |Cite
|
Sign up to set email alerts
|

GnRH antagonists may affect endometrial receptivity

Abstract: Study objective-HOXA10 is an essential regulator of endometrial receptivity. To determine the effect of gonadotropin releasing hormone (GnRH) antagonists on endometrial receptivity we assessed endometrial HOXA10 expression in GnRH antagonist, GnRH agonist, and natural cycles. Design-Prospective case-control study Setting-University academic medical centerPatients-Nineteen subjects were included: 12 subjects underwent controlled ovarian hyperstimulation (COH) with recombinant follicle stimulating hormone (rFSH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 53 publications
7
52
0
2
Order By: Relevance
“…In this regard, a recent meta analysis comparing outcomes between antagonist and agonist cycles, including 13 randomized clinical trials with a range of 2-101 pregnant cases for each study, miscarriage rates were not found to be different (11.7% vs 11.5%) [18]. However, the studies in this meta analysis in the Cochrane review did not take into account the plurality of gestations and the definitions of miscarriage were not uniform [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Short Communicationmentioning
confidence: 83%
See 1 more Smart Citation
“…In this regard, a recent meta analysis comparing outcomes between antagonist and agonist cycles, including 13 randomized clinical trials with a range of 2-101 pregnant cases for each study, miscarriage rates were not found to be different (11.7% vs 11.5%) [18]. However, the studies in this meta analysis in the Cochrane review did not take into account the plurality of gestations and the definitions of miscarriage were not uniform [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Short Communicationmentioning
confidence: 83%
“…In order to determine whether this subtle clinical outcome difference between those GnRH analogues could be integral to endometrial microenvironment, some studies addressed endometrium as a confounding factor. Histologically no apparent differences were found enough to detect any deleterious effects of GnRH antagonists; others found significant ultrastructural differences such as different expressions of growth factors and chemokins from endometrial cells exposed to GnRH agonists and antagonists [9][10][11][12]. Bearing in mind that GnRH receptors exist on endometrium, it may be speculated that endometrial factor could be related to this clinical outcome difference between GnRH agonists and antagonists.…”
Section: Short Communicationmentioning
confidence: 99%
“…The study of Rackow showed that endometrial receptivity is decreased in cycles with GnRH antagonist use (Rackow et al, 2008). This could also explain why this effect is not observed in oocyte donation cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Shapiro и соавторы, оценивая эндометрий в стимули-рованных циклах ЭКО в сравнении с натуральным циклом, обнаружили преждевременную секреторную трансфор-мацию и изменение экспрессии маркеров рецептивности в постовуляторной и ранней лютеиновой фазе, что, воз-можно, приводит к несинхронному взаимодействию меж-ду жизнеспособным эмбрионом и рецептивным или суб-рецептивным эндометрием [23]. Кроме того, по данным исследователей, в лютеиновой фазе стимулированного цикла изменяется профиль экспрессии генов эндометрия [24]. В описанных протоколах с антагонистом гонадотро-пин-рилизинг гормона (ГнРГ) снижается экспрессия генов НОХА 10 в строме эндометрия.…”
unclassified
“…При анализе экспрессии НОХА 10 в эндометрии в стиму-лированных циклах в протоколах с ант-ГнРГ и а-ГнРГ изменения экспрессии этого гена обна-ружены не были [12]. Вместе с тем известные исследователи B. Rackow и коллеги предпола-гают, что ант-ГнРГ снижают экспрессию НОХА 10 в строме эндометрия [24]. Поэтому пациент-кам с неудачами имплантации в анамнезе перед проведением программы ВРТ ЭКО не-обходимо провести анализ всех индукторов, влияющих на эндометрий, морфологический пейзаж эндометрия, экспрессию рецепторов Е2 и прогестерона, пиноподии, интегрины, молекулярно-генетические аспекты эндомет-рия в стимулированных циклах.…”
unclassified